2002
DOI: 10.1074/mcp.m200067-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Attomole Detection of in Vivo Protein Targets of Benzene in Mice

Abstract: Modified proteins were detected in liver and bone marrow of mice following treatment with [ 14 C]benzene. Stained sections were excised from one-dimensional and twodimensional gels and converted to graphite to enable 14 C/ 13 C ratios to be measured by accelerator mass spectrometry. Protein adducts of benzene or its metabolites were indicated by elevated levels of 14 C. A number of proteins were identified by in-gel proteolysis and conventional mass spectrometric methods with the low molecular weight proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Protein binding in liver and kidney exhibited approximate linearity with dose whereas in the bladder non-linearity was observed. No DNA adducts were detected in the bladder supporting the hypothesis for this compound that bladder cancer induction arises through regenerative hyperplasia rather than through a genotoxic mechanism [27].…”
Section: Macromolecular Adductssupporting
confidence: 52%
See 1 more Smart Citation
“…Protein binding in liver and kidney exhibited approximate linearity with dose whereas in the bladder non-linearity was observed. No DNA adducts were detected in the bladder supporting the hypothesis for this compound that bladder cancer induction arises through regenerative hyperplasia rather than through a genotoxic mechanism [27].…”
Section: Macromolecular Adductssupporting
confidence: 52%
“…In addition to binding to DNA, substantial protein modification was seen after benzene exposure [27]. Liver and bone marrow proteins were run out on one dimensional and two dimensional gels, bands excised and analysed by AMS.…”
Section: Macromolecular Adductsmentioning
confidence: 99%
“…Validation in this context would focus on estimation of key parameters that are feasible to measure in a 1-year time-frame in a series of short-term experiments using human volunteers under an IRBand USEPA-HSRB-approved study protocol. These experiments would involve controlled administration of approximately 1 part per trillion of 14 C-radiolabeled naphthalene in air (i.e., a concentration that is a fraction of ambient levels of naphthalene typically found in indoor air, as discussed in Griego et al, 2008 by inhalation for 6 h. Naphthalene and metabolites in blood and urine at these exposure levels can be analyzed readily by accelerator mass spectrometry (AMS) (see, e.g., Bogen et al, 1998;Dingley et al, 1998;Williams et al, 2002;Cupid et al, 2004). Measured samples should include at least hourly blood samples.…”
Section: In Vivo Studies Are Needed To Validate a Human Pbpk Model Fomentioning
confidence: 99%
“…These studies also provided some degree of cross-validation, as many of the proteins identified were targets of multiple electrophiles. Williams et al (51) applied highly sensitive accelerator mass spectrometry (AMS) to detect 14 C enrichment in proteins from liver and bone marrow of mice after treatment with [ 14 C]benzene. The overall approach was analogous to that described above, except that AMS analysis detected attomolar levels of 14 C. The detection of radiolabels associated with histones in bone marrow samples led them to analyze proteolytic digests by AMS, and 14 C label was found to be widely distributed across the protein sequences analyzed.…”
Section: Proteomics Approaches To Identify Protein Targets Of Electromentioning
confidence: 99%